Stakeholders’ views on vocational rehabilitation programs: a call for collaboration with Occupational Health Physicians - Mattei, Giorgio; Sacchi, Valentina; Alfieri, Salvatore; Bisi, Antonella; Colombini, Niccolò; Ferrari, Silvia; Giubbarelli, Giuseppe; Gobba, Fabriziomaria; Modenese, Alberto; Pingani, Luca; Rigatelli, Marco; Rossetti, Marisa; et al. (La Medicina del Lavoro, 2018)
Background: The triple-dip recession taking place in Italy in 2008-2014 impacted negatively on health, mainly by increasing the rate of unemployment. This increased the prevalence of mental health disorders, while reducing the number of available places on vocational rehabilitation programs (VRPs) delivered by the psychiatric services. Objectives: To explore the different points of views of stakeholders (namely, users and professionals) involved in VRPs developed inside an Italian Community Mental Health Center (CMHC). Methods: A sample of users, psychiatrists, educators and nurses of an Italian CMHC involved in VRPs took part in a focus group. Content analysis was performed with MAXQDA 12, by developing a hierarchical code system a posteriori (i.e., derived from the data). The respondent validation phase was carried out by means of a multiple-choice questionnaire, administered to all participants. Results: A total of 86 emerging issues were coded, divided into two macro-areas: Positive and Negative Reinforcements (48 contributions, 56%, and 38 contributions, 44%, respectively), further subdivided into three areas: professional (service) factors, personal (i.e, user-related) factors, and work environment features (including relationships in the workplace). Some contributions raised issues concerning occupational health protection (e.g. need of information about the rights and duties of the users-workers, as well as the risks they are exposed to in the workplace). Conclusions: The analysis suggested to address specific issues concerning work and VRPs by means of psycho-education group interventions currently carried out at CMHCs, and pointed to the need to foster collaboration between mental health professionals and the occupational health physician of the company where the VRP is started and where the user might be employed.